2019
DOI: 10.1002/bmc.4694
|View full text |Cite
|
Sign up to set email alerts
|

Determination, residue and risk assessment of trifloxystrobin, trifloxystrobin acid and tebuconazole in Chinese rice consumption

Abstract: A simple and rapid analytical method for the detection of trifloxystrobin, trifloxystrobin acid and tebuconazole in soil, brown rice, paddy plants and rice hulls was established and validated by liquid chromatography with tandem mass spectrometry. Acceptable linearity (R2 > 0.99), accuracy (average recoveries of 74.3–108.5%) and precision (intra‐ and inter‐day relative standard deviations of 0.9–8.8%) were obtained using the developed determination approach. In the field trial, the half‐lives of trifloxystrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, TFSA only had good recoveries (98–102%) using C 18 , and the average recoveries were very low (about 30%) using PSA for cleanup. Luo et al (2020) also found that PSA could retain TFSA in rice samples, leading to recoveries <35%. The primary secondary amino groups on the surface of PSA could interact with various polar organic acids (Li et al, 2016), which may be the reason for the low recovery of TFSA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TFSA only had good recoveries (98–102%) using C 18 , and the average recoveries were very low (about 30%) using PSA for cleanup. Luo et al (2020) also found that PSA could retain TFSA in rice samples, leading to recoveries <35%. The primary secondary amino groups on the surface of PSA could interact with various polar organic acids (Li et al, 2016), which may be the reason for the low recovery of TFSA.…”
Section: Resultsmentioning
confidence: 99%
“…In brief, the literature on the determination of TFS and TFSA residues mainly focused on plant matrices such as rice (Luo et al, 2020), tomato (Wang et al, 2014) and grapes (Likas et al, 2007), while there are few studies on the residues of TFS and its metabolite in animal‐derived food. Han, Sun, and Wu (2008) developed a method for the determination of TFS and TFSA by gas chromatography in peanut oil, milk and juices.…”
Section: Introductionmentioning
confidence: 99%
“…Trifloxystrobin (TFS, methyl-a-methoxyimino-2-((1-(3-(trifluoromethyl) phenyl) ethylidene ((amino) oxymethyl)-benzeneacetate)), a systemic broad-spectrum foliar fungicide synthesized from the natural antibiotic strobilurin with an oximether side chain, is widely used to control fungi in greenhouses, nurseries, orchards, vegetable gardens, and paddy fields ( Zhu et al, 2015b ). Due to its rapid degradation in plants, soil, and water, as well as its long-lasting effects and resistance to rain, it occupies an important position among strobilurins ( Luo et al, 2020 ). However, the widespread application of TFS has raised serious public health concerns, in particular, that the potential off-site transport of environmental residues could have non-target toxic effects on humans and wildlife ( Liu et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Pyraclostrobin (Figure ) is one of the most widely consumed strobilurin fungicides in China and is safe for use in fruits and food crops, such as grape, pear, rice, and tomato . There was rather low dietary intake risk when this fungicide was scientifically used. Pyraclostrobin can control a number of plant diseases because of its satisfactory broad-spectrum activity. This fungicide is also well known for its plant health effects so that it can be used as a plant growth regulator .…”
Section: Introductionmentioning
confidence: 99%